A discourse analysis of advertisements in English and Vietnamese on the internet - Do, Van Anh.; Ngu Thien Hung, Ph.D. (Đà Nẵng : The University of Da Nang, 2012)
Introduction; Literature review and theoretical background; Method and procedure...
Master thesis in the English language. Field: The English language. Code: 60.22.15.
Keywords: English language; English language -- Discourse analysis; Internet -- Advertisement